Ecological testing results of the rice varieties of the ARC “Donskoy” in the Krasnodar Territory - P. I. Kostylev; М. А. Ladatko; Е. V. Krasnova; I. А. Zeleneva; B. V. Foliyants; А. V. Aksenov (Зерновое хозяйство России)
In order to increase gross harvest and productivity of rice, the development of new varieties and their timely use in production is of great importance. The Federal Research Center of Rice and Agricultural Research Center “Donskoy” regularly develop more productive varieties with improved resistance to diseases and other factors. Each variety forms a specific response to various agro-ecological conditions, which affects productivity, which is the main indicator of cost and demand in crop production. The purpose of the current study was a joint ecological testing of new rice varieties, developed in the Agricultural Research Center “Donskoy” in the growing conditions of the Krasnodar Territory jointly with the Federal Research Center of Rice. The study has revealed significant differences in the productivity. The yields of rice varieties varied significantly depending on the variant of the trial. In the ESOS “Krasnaya” the variety ‘Kapitan’ sown after three forecrops and with two variants of fertilizing was the best one, forming 7.26 t/ha and exceeding the standard variety ‘Rapan’ on 0.37 t/ha. In the RPZ “Krasnoarmeisky”, the variety also produced the maximum yield (7.11 t/ha). In 2021, the variety ‘Kapitan’ produced 8.47 t/ha in the JSC “Agrocomplex Rossiya” and 5.00 t/ha in the AF “Kuban” at the level of the new standard ‘Rapan 2’. The productivity of the studied varieties highly positively correlated with the traits ‘length of panicle’ (r = 0.83±0.13), ‘1000-kernel weight’ (r = 0.97±0.10), ‘kernel weight per panicle’ (r=0.97±0.15); there was a mean positive correlation with the traits ‘plant height’ (r = 0.67±0.20) and ‘number of productive stems per area unit’ (r = 0.59±0.18). In the ecological testing in four farms, rice productivity was closely positively correlated with each other (r was from 0.804 to 0.999) with large differences in absolute values. For cultivation in the Krasnodar Territory there has been recommended a high-productive variety ‘Kapitan’ of joint breeding of the ARC “Donskoy” and the FSC of Rice.